1997
DOI: 10.1172/jci119479
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical enhancement of atherosclerosis by probucol treatment in apolipoprotein E-deficient mice.

Abstract: Dietary administration of probucol (0.5%, wt/wt) efficiently reduced total plasma cholesterol levels in apolipoprotein E-deficient mice (apoE Ϫ / Ϫ ) by 40%, with decreases in high density lipoprotein (HDL) and apoAI by 70 and 50%, respectively. Paradoxically, however, aortic atherosclerotic plaques in the probucol-treated apoE Ϫ / Ϫ mice formed more rapidly than in the untreated apoE Ϫ / Ϫ mice, and the lesions were two to four times larger and more mature regardless of sex, age, and genetic background ( P Ͻ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
65
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 37 publications
11
65
6
Order By: Relevance
“…Consistent with previ-ous findings, 25,35 lesions were found at all sites and covered large areas of the vessel, with the exception of the descending thoracic aorta, where lesions were smaller and located around the ostia of the branching intercostal arteries. Although a detailed compositional analysis was not made, the lesion morphology was grossly similar in all regions, with necrotic cores containing cholesterol crystals observed regularly at all sites.…”
Section: Aortic Morphometrysupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previ-ous findings, 25,35 lesions were found at all sites and covered large areas of the vessel, with the exception of the descending thoracic aorta, where lesions were smaller and located around the ostia of the branching intercostal arteries. Although a detailed compositional analysis was not made, the lesion morphology was grossly similar in all regions, with necrotic cores containing cholesterol crystals observed regularly at all sites.…”
Section: Aortic Morphometrysupporting
confidence: 90%
“…Previous studies have reported that probucol enhances lesion formation in the aortic root of female and male apoEϪ/Ϫ mice fed normal chow. 25,26 Consistent with that finding, lesions at this site were larger in probucol than control male mice fed a high-fat chow (Table I), although this difference did not reach statistical significance. Lesion size in the aortic root varied in the probucol group (Table I) owing to 2 animals with no lesions at all (not shown), whereas all other drug-treated animals had larger lesions than the largest individual control mouse.…”
Section: Aortic Morphometrysupporting
confidence: 80%
See 2 more Smart Citations
“…For example, probucol, which inhibits the oxidative modification of LDL, prevented the development of atherosclerotic lesions in WHHL rabbits (17,18), but increased atherosclerotic lesions 2 to 4 times in apolipoprotein E-deficient mice as compared with control mice (19). These findings suggest that the effects of antioxidants on atherosclerosis may be species specific.…”
Section: Discussionmentioning
confidence: 91%